95.2k views
2 votes
Simplify 3×+1(2×-1)2-1(6×)​

User Dalal
by
6.2k points

1 Answer

4 votes

●✴︎✴︎✴︎✴︎✴︎✴︎✴︎✴︎❀✴︎✴︎✴︎✴︎✴︎✴︎✴︎✴︎✴︎●

Hi my lil bunny!

❧⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯☙

Answer =
\boxed {x - 2}


3x +1(2x-1)2-1(6x)

=
\boxed {3x + 1 . ( 2x - 1 ) . 2 - 1 (6x) = x - 2}

Steps :


3x + 1 . (2x - 1) . 2 - 1 . (6x)

Remove the parentheses :
(a) = a


= 3x + 1 * (2x- 1) * 2 - 1 * 6x

Multiply the numbers :
1 * 2 = 2


= 3x + 2 ( 2x - 1 ) * 6x

Multiply the numbers :
1 * 6 = 6


= 3x + 2 ( 2x - 1 ) -6x

Expand:
2 (2x - 1) : 4x - 2


2 ( 2x - 1 )

Apply the distributive law :
a (b - c) = ab - ac


a = 2, b = 2x, c = 1 \\= 2 * 2x - 2 * 1

Simplify
2 * 2x - 2 * 1 : 4x - 2

=
= 4x - 2


= 3x + 4x - 2 - 6x

Simplify
3x + 4x - 2 - 6x : x - 2

=
x - 2

❧⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯☙

●✴︎✴︎✴︎✴︎✴︎✴︎✴︎✴︎❀✴︎✴︎✴︎✴︎✴︎✴︎✴︎✴︎✴︎●

Have a great day/night!

❀*May*❀

User Derp
by
5.1k points